Study on Synthesis and Application of HC\({_s}_5\)P\({_2}\)W\({_1}_8\)O\({_6}_2\).16H\({_2}\)O to Adsorption of Organic Matter: Methylene Blue - Koraichi, Salim; Belghiche, Robila; Abbessi, Mostefa (New Innovations in Chemistry and Biochemistry Vol. 1, 2021)
The adsorption of a dye, methylene blue, by a cesium Dawson heteropolyanion HCs5P2W18O62.16H2O, was investigated. In heterogeneous catalysis, adsorption is a crucial step. Adsorption can also be used as a separation process to remove colours that may be present in industrial waste. The first part deals with the synthesis and the characterization of adsorbent. The experimental parameters affecting the adsorption were then optimized. The regeneration of the adsorbent was finally studied. The optimal yield found was 88% for a MB concentration of 25 mg/L and an adsorbent mass of 0.25 g. The yield of the regeneration was 98%, at 80°C. Adsorption isotherms linearization has showed that it is the Langmuir model best suited to describe the considered phenomenon, thus, reflecting a good distribution of active sites across the adsorbent surface.